Microspheres based on mannosylated lysine-co-sodium alginate for macrophage-specific delivery of isoniazid - Tiwari S.; Chaturvedi A.P.; Tripathi Y.B.; Mishra B. (My University, 2025)
The present investigation reports coupling of ε- and α-amino groups of lysine (LS) with mannose (m-LS) and sodium alginate (SA), respectively, to reduce its toxicity. Prepared conjugate, m-LS-co-SA, was characterized through infra-red spectroscopy and differential scanning calorimetry. Cell viability studies were undertaken to assess the safety profile of the prepared conjugate. Microspheres, based on the conjugate, were prepared using spray drying technique and studied for targeting of isoniazid to alveolar macrophages (AMs). Pharmacokinetic studies of the optimized formulation batch were performed in Charles Foster rats. Infra-red spectral data of the synthesized conjugate were in agreement to the presumptive sequence of the conjugation process. Dispersibility, thermal stability and safety of the conjugate were conducive to its biomedical application. Microspheres, formulated from the conjugate, were of uniform size and offered satisfactory drug loading efficiency and in vitro release characteristics. X-ray diffraction studies established that drug was entrapped within the microspheres rather than being adsorbed on to the surface. Pharmacokinetic studies revealed that the conjugate could be a potential vehicle towards both active targeting of isoniazid to AMs and controlling its release rate. © 2011 Elsevier Ltd. All rights reserved.